A homeostatic mechanism rapidly corrects aberrant nucleocytoplasmic ratios maintaining nuclear size in fission yeast - Cantwell, Helena (J Cell Sci, 2019)
Nuclear size scales with cell size across a wide range of cell types. The mechanism by which this scaling is maintained in growing cells remains unclear. Here, we investigate the mechanism of nuclear size homeostasis in the simple eukaryote fission yeast, by monitoring the recovery of aberrant nuclear volume to cell volume (N/C) ratios following perturbation. We demonstrate that both high and low N/C ratios correct rapidly, maintaining nuclear size homeostasis. We assess the kinetics of nuclear and cellular growth and of N/C ratio correction, and demonstrate that nuclear and cellular growth rates are not directly coupled. We propose that the mechanism underlying nuclear size homeostasis involves multiple limiting factors implicated in processes including nucleocytoplasmic transport, lipid biogenesis and RNA processing. We speculate that these link cellular size increases to changes in nuclear contents, which in turn lead to changes in nuclear membrane surface area. Our study reveals that there is rapid nuclear size homeostasis in cells, informing understanding of nuclear size control and size homeostasis of other membrane-bound organelles.